Energy-Efficient Scheduling in WMSNs - Watfa, Mohamed K.; Shahla, Farah Abou (INFOCOMP Journal of Computer Science, 2009)
Recent technological breakthroughs in ultra-high integration and low-power electronics have enabled the development of tiny battery-operated sensors. The signal processing and communication activities are the main consumers of sensor’s energy. Since sensors are battery-operated, keeping the sensor active all the time will limit the battery’s lifetime. Therefore, optimal organization and management of the sensor network is crucial in order to perform the desired function with an acceptable level of quality and to maintain sufficient sensor energy for the required mission. Wireless multimedia sensor networks (WMSN) are a new and emerging type of sensor networks producing multimedia content. These networks have the potential to enable a large class of applications. Many such applications require mechanisms to efficiently deliver application level quality of service (QoS) and to map these requirements into network layer metrics such as latency and jitter. Thus an efficient scheduling algorithm that differentiates between levels of services by providing QoS guarantees is needed. Since WMSNs are battery-constrained, the algorithm should take into consideration energy-efficiency as well. In this paper, we present a scheduling algorithm that takes into account the promptness of real-time multimedia streaming. The algorithm divides the frame into slots and assigns the slots to different nodes. We also present an algorithm to interleave the slots in a way to minimize jitter. We have evaluated the interleaving algorithm using Matlab and found that it minimizes the jitter for all nodes in a consistent way while keeping the overhead generated to a certain limit.